Prevention and control of spontaneous combustion/fire in coal stockpiles of power plants using firefighting chemicals. Issue 10 (3rd October 2022) - Mohalik, Niroj Kumar; Ray, Santosh Kumar; Mishra, Debashish; Pandey, Jai Krishna; Mondal, Somu; Khan, Asfar Mobin; Singh, Ranvijay Kumar
ABSTRACT: Spontaneous combustion of coal in stockpiles of power plants has a significant problem worldwide which leads to several health hazards, environmental pollution and coal loss. Spontaneous combustion coal stockpiles depend on both endogenous (coal characteristics) and exogenous parameters (stockpile geometry, wind speed, wind direction, local temperature). This paper describes the laboratory experiments to study the suitability of firefighting chemicals on the spontaneous combustion/fire of coal in stockpiles. Coal samples were collected from four different heaps of coal laid in coal storage yards of Talwandi Sabo Power Limited (TSPL), Punjab. This study comprises laboratory analysis i.e., proximate analysis, ultimate analysis, critical oxidation temperature, differential scanning calorimetry (DSC) analysis, gross calorific value (GCV), particle size analysis, and field studies i.e., thermal monitoring of fire-affected area before and after firefighting chemicals. Experiments on mixtures of coal and firefighting chemical having compositions viz. 1, 2, 3, and 5%, were carried out using DSC study for optimization of inhibitors as well as its efficacy. During the laboratory study the chemical composition of 3% was found to be optimum for field application to extinguish coal stockpile fire.